Transformation: Towards what kind of agriculture? Plant protection products and non-conventional farming models in the European Union - Pastorino, Leonardo (Przegląd Prawa Rolnego, 2022)
In the light of the environmental and climate crisis, as well as bearing in mind the efforts that the European Union has been undertaking to shift to a model of sustainable development and agri-food production at a general level, while taking into account that in this context the problem of the use of plant protection products is pivotal and subject to constant reflection and correction, this work focuses on three objectives: (1) to propose a conceptual and critical approach to the different paradigms and models of agriculture and its development, on the assumption that none of them has met with total support and that it is difficult to define a model of sustainable agricultural production; (2) to present a legal framework, at least at EU level, on plant protection products, in order to encourage further development of this framework in relation to sectoral legislation relating explicitly to agriculture, given the current state of research and amendments; (3) to compare the legislation on agricultural models with that on plant protection products and to examine how the two coexist.